Parametric Analysis of a Low Profile UWB Trapezoidal Antenna for Ultra Wireless Communication System - Noor Zirwatul Ainee, Naharuddin; Nurul Hazlina, Noordin (Springer International Publishing, 2015)
This paper presents the analysis of CPW—fed trapezoidal monopole antenna with return loss lower than −10 dB and VSWR lower than 2. The proposed antenna operates from 2.2 to 11.5 GHz and is suitable for ultra wideband applications. This antenna consists of a ground plane, a feed line and a trapezoidal radiating structure. The trapezoidal shaped patch is chosen because of its simple structure, which reduces the complexity of its geometrical optimization process. Initially the proposed antenna is designed with a single trapezoidal shaped patch and later additional structures were loaded at the bottom of the patch. With a total size 38 mm × 51 mm × 1.6 mm and designed on a substrate with dielectric constant 4.4, the antenna satisfies the licensed frequency band of S band (2–4) GHz, C band (4–8) GHz and X band (8–12) GHz application.